Self-Energy Function of States of a Quantum Dot Tunnel Coupled to Leads - R.Kh. Gainutdinov; M.A. Khamadeev; M.R. Mohebbifar; A.A. Mutygullina (Учёные записки Казанского университета: Серия Физико-математические науки)
Quantum fluctuations of a single-electron transistor consisting of a quantum dot tunnel coupled to noninteracting leads are investigated. It is shown that an approach based on the generalized dynamical equation allows to obtain corrections for the system energies that can not be deduced from the standard theory.